Improved optical properties of BN powder shielded Ce:YAG ceramics prepared by hot pressing. Issue 16 (15th August 2022) - Pang, Qingle; Liu, Wenlei; Shen, Jianxing; Wang, Tailin; Cheng, Chuanbing; Liu, Yuanhui; Han, Xiujun
Abstract: Yttrium aluminum garnet (YAG) phosphor transparent ceramics prepared via vacuum hot pressing (HP) suffer from carbon contamination owing to the graphite mould used in the HP system. The conventional method was to dope LiF as a decarburizing agent, but carbon contamination cannot be effectively prevented when preparing Ce:YAG ceramics via a solid-phase reaction combined with HP sintering. In this study, we report the fabrication of highly transparent Ce:YAG ceramics via HP sintering with a flexible hexagonal boron nitride (BN-h) wrapping, which prevents carbon contamination of the samples caused by the graphite mould used in the process. High-transmittance Ce:YAG ceramics were prepared at a medium temperature of 1600 °C and a low vacuum pressure of 10 −1 Pa.